(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The theory of loneliness is a concept that explains how socio-psychological isolation can lead to negative consequences for a person’s mental health. According to this theory, loneliness can be caused not only by physical separation from other people, but also by a lack of emotional connection with others. Loneliness can lead to increased levels of stress and anxiety, which in turn can lead to the development of depression and other mental disorders. Often people suffering from social isolation begin to experience a lack of self-sufficiency and self-confidence, which can lead to a feeling of helplessness and hopelessness. In order to avoid the negative consequences of social isolation and loneliness, it is important to find time to communicate with other people and establish emotional connections. It is also useful to work on strengthening your self-esteem and self-confidence in order to feel comfortable in the company of other people.